Enhancing nutrition-majored students' reflective judgment through online collective reflection. (November 2017) - Lord, Asta Y.Z.; Chen, Ming-Puu; Cheng, Yu-Yao; Tai, Ku-Chou; Pan, Wen-Harn
Abstract: Reflective judgement is a critical capability for dietitians since they are often confronted with contradictory evidence and conflicting viewpoints. The lack of reflective judgment literature for nutrition education revealed an imperative need to find ways to enhance nutrition-majored students' reflective judgement. Thus, this study aimed to employ online reflection strategy to enhance nutrition-majored students' reflective judgment performance. One hundred and twenty nutrition-majored college juniors participated in the four-week experimental online reflective judgment learning activity. The independent variable was the type of online reflection strategy (the collective reflection using branched threading, the collective reflection using linear threading, and self-reflection) while the dependent variables included reflective judgement performance and participants' perceived learning. The results indicated that all of the three online reflection strategies promoted learners' reflective judgment performance equally with an increment of 0.75 stage. Participants showed positive perceptions toward reflective judgement learning. Further research is needed to better understand the long-term impact of the online collective reflection strategies in the real-world practice of dietetics. Highlights: Online reflection strategies promoted nutrition-majored learners' reflective judgment. Nutrition-majored learners positively perceived online reflective judgment learning. Long-term effects of online reflection strategies need to be further examined.